2006
DOI: 10.1292/jvms.68.405
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Efficacies of Oseltamivir Carboxylate and Zanamivir against Equine Influenza A Viruses

Abstract: ABSTRACT. To investigate the possibilities of two NA inhibitors [oseltamivir carboxylate (OC) and zanamivir (ZA)] as the clinical agents for equine nifluenza A virus (EIV) infection, we examined the efficacies of these inhibitors against twelve EIVs in vitro. OC and ZA inhibited NA activities of all EIVs with 50% inhibitory concentrations with ranging from 0.017 to 0.130 and from 0.010 to 0.074 μM, respectively. OC and ZA inhibited plaque-forming of all EIVs in MDCK cells with 50% effective concentrations with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Whether IC 50 or EC 50 as determined in vitro correlates more closely with the efficacy of OC against EIV in horses has not been established at present. Therefore, it would be safer for veterinarians to retain the concentration of OC above 36.9 ng/ml, which was the highest value for IC 50 s and EC 50 s of the EIV strains as determined in vitro [9]. Therefore, when veterinarians choose 2.0 mg/kg as an oral dose of oseltamivir, the administration intervals should be less than 10 hr (trough concentration: 37.2 ng/ml) in order to retain the concentration of OC above 36.9 ng/ml (Fig.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…Whether IC 50 or EC 50 as determined in vitro correlates more closely with the efficacy of OC against EIV in horses has not been established at present. Therefore, it would be safer for veterinarians to retain the concentration of OC above 36.9 ng/ml, which was the highest value for IC 50 s and EC 50 s of the EIV strains as determined in vitro [9]. Therefore, when veterinarians choose 2.0 mg/kg as an oral dose of oseltamivir, the administration intervals should be less than 10 hr (trough concentration: 37.2 ng/ml) in order to retain the concentration of OC above 36.9 ng/ml (Fig.…”
mentioning
confidence: 98%
“…1) [3]. We first reported that OC inhibits the neuraminidase (NA) activities and plaque-forming of several EIV strains in vitro [9]. Subsequently, we reported the therapeutic and prophylactic efficacies of oral administration of oseltamivir in horses experimentally infected with EIV [10].…”
mentioning
confidence: 99%
See 3 more Smart Citations